Redesigning the Patiayam Kudus Archaeological Museum with a Regionalism Architecture Approach - Muhammad Sulthon (HM Publisher, 2021)
Regionalism architecture is architecture that advocates the appearance of buildings that are the result of a compound of internationalism with modern cultural and technological patterns, values, and nuances of tradition that are still adhered to by the local community. This study aimed to describe the redesign of the Patiayam archaeological museum, which is better able to collect, accommodate, maintain, and exhibit as a whole the prehistoric relics found at the Patiayam Site. This research is descriptive research. This method describes, and explains the design requirements and design determinants of the planning and design of the Patiayam Archaeological Museum, Kudus, Central Java. The style of the house building joglo Kudus as a form of local architectural style will become the basic idea of regionalism architecture in the design of the Patiayam Kudus museum. The shape of the façade of the main museum building adopts the typical shape of the traditional joglo Kudus house but has undergone changes in the development of detailed forms due to the difference in the size scale of the joglo Kudus house and the museum building, which is larger in size. In conclusion, the architectural concept of regionalism increases the functionality of the Patiayam Kudus archaeological museum as a means of educating about ancient sites.